1989
DOI: 10.1136/gut.30.10.1344
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectrometry for faecal fat measurement: comparison with conventional gravimetric and titrimetric methods.

Abstract: SUMMARY This investigation was aimed at comparing a new method for measuring faecal fat excretion, carried out with a semi-automated instrument by using near infrared analysis (NIRA), with the traditional titrimetric (Van de Kamer) and gravimetric (Sobel) methods. Near infrared analysis faecal fat was assayed on the three day stool collection from 118 patients (68 chronic pancreatitis, 19 organic diseases of the gastrointestinal tract, 19 alcoholic liver disease, 12 functional gastrointestinal disorders). A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 4 publications
3
22
0
Order By: Relevance
“…The necessary analytical procedures are, however, often complex and time consuming. Recently, near-infrared re¯ec-tance (NIR) spectroscopy has been introduced as an alternative to or even a replacement for the traditional chemical methods for nutrient measurements in stools (Benini et al, 1989(Benini et al, , 1992 and foods (Lanza, 1983). NIR spectroscopy is a rapid, non-destructive method, which has found widespread use in compositional analyses such as fat, protein, water and carbohydrates (Osborne & Fearn, 1986;Williams & Norris, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The necessary analytical procedures are, however, often complex and time consuming. Recently, near-infrared re¯ec-tance (NIR) spectroscopy has been introduced as an alternative to or even a replacement for the traditional chemical methods for nutrient measurements in stools (Benini et al, 1989(Benini et al, , 1992 and foods (Lanza, 1983). NIR spectroscopy is a rapid, non-destructive method, which has found widespread use in compositional analyses such as fat, protein, water and carbohydrates (Osborne & Fearn, 1986;Williams & Norris, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…To measure the fecal fat concentration, five small samples were obtained from different parts of a single movement. We have already shown that the mean of at least five fat measurements from a single movement is always within ± 10% of the results found after its homogenization [23]. To calculate the mean daily fat excretion, the stool collections of the 3 days were weighed and accurately mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Despite an adequate clinical response of malabsorption and steatorrhea in patients receiving PES, malnutrition may persist. Fecal fat estimation is considered the most reliable measure of fat malabsorption and various techniques ranging from clinical observation 106 to the gold standard measures such as the van de Kramer method, 107 the near infrared spectrometry 108 and Nuclear magnetic Resonance (NMR) spectrometric fecal fat analysis 109 have been described. Indices such as the coefficient of fat absorption ((ingested fat -excreted fat)/ingested fat *100), and daily fat excretion (excreted fat/ingested fat * 100) can be derived from dietary and fecal fat estimation.…”
Section: Dovepressmentioning
confidence: 99%